2005
DOI: 10.1161/01.cir.0000153812.64956.ef
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Can Be Genetically Modified to Produce Excitable Cells Capable of Electrical Coupling

Abstract: Background-Cardiac conduction occurs in an electrical syncytium of excitable cells connected by gap junctions.Disruption of these electrophysiological properties causes conduction slowing or block. Depending on the location of affected cells within the heart, this has the potential to result in clinical syndromes such as atrioventricular block. With a view to developing gene therapy strategies for repairing cardiac conduction defects, we sought to establish whether the phenotype of fibroblasts can be modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(78 citation statements)
references
References 17 publications
(14 reference statements)
4
72
1
1
Order By: Relevance
“…1 In an earlier study, we demonstrated that fibroblasts can be genetically modified to produce excitable cells capable of electrical coupling. 2 In this study, fibroblasts were transduced with a MyoDencoding lentiviral vector to force differentiation into skeletal myotubes, resulting in the acquisition of an excitable phenotype. Gap junctional intercellular communication (GJIC) was achieved by transduction with a connexin43 (Cx43)-encoding vector.…”
mentioning
confidence: 99%
“…1 In an earlier study, we demonstrated that fibroblasts can be genetically modified to produce excitable cells capable of electrical coupling. 2 In this study, fibroblasts were transduced with a MyoDencoding lentiviral vector to force differentiation into skeletal myotubes, resulting in the acquisition of an excitable phenotype. Gap junctional intercellular communication (GJIC) was achieved by transduction with a connexin43 (Cx43)-encoding vector.…”
mentioning
confidence: 99%
“…In the study by Kizana et al, 22 no direct electrophysiological measurements were made. Action potentials were not recorded, and the proposed transmembrane currents were not demonstrated by patch-clamp techniques.…”
Section: See P 394mentioning
confidence: 98%
“…In cell cocultures, cardiomyocytes and fibroblasts can form functional gap junctions, 19,20 and recently, functional fibroblast-to-myocyte gap junctional coupling has also been demonstrated in the native rabbit sinoatrial node. 21 In this issue of Circulation, an article by Kizana et al 22 advocates the prospect that conduction defects in the heart might be repaired by genetic modification of fibroblasts. Human dermal fibroblasts were cultivated from pediatric skin samples and modified by lentivirus vector-mediated gene transfer to express MyoD, a skeletal myogenic determination factor.…”
Section: See P 394mentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to manipulate cells ex vivo to direct them towards a desired phenotype are gaining momentum, and these will hopefully help to mitigate inflammation and Regenerative therapy for cardiovascular disease ED de Muinck et al scarring as well as the propensity for life threatening arrhythmia. 77,78 Homing and engraftment of circulating cells and the microenvironmental cues that dictate survival and proliferation of cells are areas that are anticipated to see a sustained scientific commitment, and as a result of this the application of implantable scaffolds to serve as an optimized microenvironment for cell survival, differentiation and proliferation may become an important adjunct to cardiac cell therapy. [79][80][81] …”
Section: Prospectsmentioning
confidence: 99%